Flexural properties of natural fiber filled high density Polyethylene (HDPE) composites - Azlin Fazlina, Osman (Universiti Sains Malaysia (USM), 2009)
Organized by School of Materials and Mineral Resources, Universiti Sains Malaysia (USM), 26th - 27th November 2008 at Naza Hotel, Penang.